ASSESSMENT OF MICROBIAL LOAD ON PAKISTANI CURRENCY (The Research of Medical Science Review, 2025)
Previous researches on currency notes and coins established a link in spread of infectious diseases. The overall objectives of this study were to isolate, identify and characterizations of coliform bacteria from Pakistani currency in Lahore. The samples were collected from currency notes and coins from September, 2024 to February, 2025. Total 200 specimens including one hundred and seventy-five currency notes and coins (each note worth 10, 20, 50 and 100; each coin worth 1, 2 and 5) were collected from Meat & Chicken shops, Milk shops, Bakeries, Pharmacy and General stores, respectively. As a negative control 25 new currency notes (each worth 10 rupees) collected from Muslim Commercial Bank (MCB), Iqbal Town, Lahore. Currency notes and coins were aseptically transferred to laboratory before further use. The currency notes and coins were transferred into enrichment culture containing 10ml nutrient broth, separately. The enrichment culture containing currency notes were incubated at 370C for 24 hours. After incubation, the enrichment broth was sub-cultured on EMB and MacConkey agar. After incubation at 370C for 24 hours, the bacteria were purified and identified by using biochemical test and API (analytical profile index) kit. Meat, chicken, milk shops and bakeries showed 100% contamination of coliform bacteria. General stores exhibited 94.3%; pharmacy 85.7% and control group were 8% positive for coliform bacteria. Among 168 (96%) positive coliform bacteria, the dominating ones were E. coli (63.7%), Klebsiella spp. (26.2%), Enterobacter spp. (7.1%), Citrobacter spp. (3.0%). The microbiological patterns of isolated coliform bacteria showed coliform bacteria were highly resistant against Cefixime, Ciprofloxacin, Ceftriaxone, Ampicillin, and sensitive against Imipenem, Meropenem, and Gentamycin. Current study indicating that the circulating money is contaminated with coliform bacteria and it could cause the spread of coliform bacteria in population which may associate with different diseases. The awareness of people towards the contaminated money may be useful to prevent life threatening infection.